Efficacy of Rituximab in a Systemic Lupus Erythematosus Patient Presenting with Diffuse Alveolar Hemorrhage - Gabriela Montes-Rivera; Grissel Ríos; Luis M. Vilá (Case Reports in Rheumatology)
Diffuse alveolar hemorrhage (DAH) is a life-threatening complication of systemic lupus erythematosus (SLE). Although infrequent, its mortality is very high. While there are no established therapeutic guidelines, DAH has been traditionally managed with high-dose intravenous (IV) corticosteroids, cyclophosphamide, and plasma exchange. The efficacy of alternative therapies such as rituximab has been described only in a few cases. Herein, we report a 25-year-old Hispanic man who presented with acute-onset SLE manifested by polyarthralgia, nephritis, seizures, pancytopenia, severe hypocomplementemia, and elevated anti-dsDNA antibodies. His disease course was complicated by DAH. His condition was refractory to high-dose intravenous (IV) methylprednisolone pulses, IV cyclophosphamide, and plasmapheresis. Given the lack of clinical response, he was started on IV rituximab 375 mg/m2 weekly for a total of four courses. He rapidly improved after the first two doses. Over the next seven months, he did not present recurrent pulmonary symptoms. Follow-up chest computed tomography did not show residual abnormalities. This case, together with other reports, suggests that rituximab is an effective therapeutic option for DAH in SLE.